Shape-memory effect in amorphous potato starch: The influence of local orders and paracrystallinity. (1st August 2016) - Chevigny, Chloé; Foucat, Loïc; Rolland-Sabaté, Agnès; Buléon, Alain; Lourdin, Denis
Highlights: Starch's intrinsic properties are taken advantage of to develop new specialty materials. Amorphous starch small-scale organization is characterized in depth. The shape-memory effect of amorphous potato starch is linked to its local structure. Abstract: In this paper, a detailed characterization of the mechanisms at the origin of the shape-memory effect in amorphous potato starch is presented. Using different treatments (annealing) and preparation methods (hot casting and extrusion), the local structures responsible for the shape-memory were disrupted, as evidenced in the first part of the article detailing the macroscopic properties: mechanical, calorimetric and shape-memory. In the second part the macromolecular scale is investigated using X-rays diffraction and CP-MAS NMR, and thus allows making the link between the structural differences and the macroscopic properties. Finally we discuss the origin of shape-memory in amorphous starch.